Case Study: Success of Social Business Models in Indonesia - Costa, Tiago; Mendes, Clara; Amin, Rafiullah (Yayasan Adra Karima Hubbi, 2025)
Social businesses have gained significant traction in Indonesia as a response to the country’s pressing social and environmental challenges. These enterprises aim to address societal issues while achieving financial sustainability, blending social impact with business goals. Despite their potential, the success factors of social business models in Indonesia remain underexplored. This study investigates the factors contributing to the success of social businesses in the Indonesian context, focusing on those that have demonstrated both social impact and financial viability. The primary objective of this study is to identify and analyze the key factors that influence the success of social business models in Indonesia. The research seeks to explore how these businesses manage to balance social missions with financial goals, and what strategies contribute to their long-term sustainability. This research employs a case study approach, analyzing the success stories of five social businesses operating in different sectors, including education, healthcare, and environmental sustainability. Data was collected through interviews with business founders, key stakeholders, and industry experts, along with secondary data from reports and publications. Qualitative analysis was used to identify common success factors and challenges faced by these businesses. partnerships with governmental and non-governmental organizations. Additionally, having a clear and impactful social mission plays a pivotal role in attracting investors and consumers. Social businesses in Indonesia can achieve both social impact and financial sustainability by adopting inclusive business models, leveraging partnerships, and staying committed to their social missions.